1999
DOI: 10.1177/1077727x99282003
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Consumer Satisfaction/Dissatisfaction with the Performance of Apparel Products

Abstract: The purpose of the study was to investigate determinants of consumer satisfaction and dissatisfaction (CS/D) with the performance of apparel products at the purchase and productconsumption stages. An experimental design was used. The sample consisted of 120 students enrolled at a university located in a metropolitan area in the midwestern United States. Results showed that performance expectation was a significant determinant of CS/D at the purchase stage. Perception of product performance and confirmation or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 22 publications
2
35
0
Order By: Relevance
“…While, in other study relate consumer dissatisfaction directly to product or performance expectation. Chen-Yu, Williams and Kincade (1999) in his study showed that performance expectation was a significant determinant of consumer dissatisfaction or satisfaction at the purchase stage. Hence, consumer dissatisfaction is seriously resulted from the discrepancy between expected and realized performance and dissatisfaction with an attribute which often arises from poor business practices (Adamson, 1991;Schouten and Van Raiij, 1990).…”
Section: Unpleasant Experiences Dissatisfaction and Complaint Behaviormentioning
confidence: 99%
“…While, in other study relate consumer dissatisfaction directly to product or performance expectation. Chen-Yu, Williams and Kincade (1999) in his study showed that performance expectation was a significant determinant of consumer dissatisfaction or satisfaction at the purchase stage. Hence, consumer dissatisfaction is seriously resulted from the discrepancy between expected and realized performance and dissatisfaction with an attribute which often arises from poor business practices (Adamson, 1991;Schouten and Van Raiij, 1990).…”
Section: Unpleasant Experiences Dissatisfaction and Complaint Behaviormentioning
confidence: 99%
“…The current literature focuses extensively on the expectancy-disconfirmation framework for explaining consumer satisfaction and dissatisfaction which states that if product expectation meets performance then there is conformance otherwise there is disconfirmation (Churchill & Surprenant, 1982). An empirical study carried out with regard to performance of apparel products in a university setting showed that performance expectation was a significant determinant of consumer satisfaction or dissatisfaction (Chen-Yu, Williams, & Kincade, 1999).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the majority of studies using the confirmation/ disconfirmation paradigm, expectations are theorised as the standard or baseline for evaluating the quality of product performance (Chen-Yu et al, 1999). Woodruff et al (1983) suggest that consumers often have experiences beyond the product that they have actually purchased and used.…”
Section: Expectations About Product Performancementioning
confidence: 99%
“…Refer to Figure 1. Whereas confirmation occurs when a product performs as expected, contributing to satisfaction or indifference (neutral feelings), positive or negative disconfirmation arises from discrepancies between prior expectations and actual performance, respectively leading to satisfaction and dissatisfaction (Swan & Combs, 1976;Oliver & DeSarbo, 1988;Chen-Yu et al, 1999;Steward in Ndubisi & Ling, 2006).…”
Section: The Expectancy Disconfirmation Paradigmmentioning
confidence: 99%
See 1 more Smart Citation